Assessment of Women’s Participation in Cooperative Societies and its Determinants in Yewa North Local Government Area of Ogun State, Nigeria - Olawale , Awotide Diran (Asian Journal of Agriculture and Rural Development, 2012)
Cooperatives have been regarded as one of the main institutional machineries for empowering the economically weak members of the society. Despite the availability of cooperative societies, it appears that a significant proportion of rural women are either unaware of the existence of such co-operative societies or are lacking in the basic socioeconomic characteristics that form the prerequisite for participation in such activities. The study therefore examined the level of participation of women in cooperative organization and its determinants in the study area. The study was conducted in Yewa North Local Government area of Ogun State, south-west rainforest zone of Nigeria in 2011 using two stage sampling techniques to select 180 respondents. Descriptive statistics and Logit regression analysis were used to analyze the data generated. The results showed that pressure from household head, insufficient fund and low membership were found to be the major problems militating against women participation in cooperatives. Logit regression analysis revealed positive and significant relationships between variables such as education, years of business experience and forms of cooperative (producers and credit and thrift) and these variables were the major determinants of participation in cooperative society. Based on the findings of this study, it is recommended that any policy that will further increase the level of education of women would increase their participation in cooperative society.